Perbandingan Performa OpenPLC dengan PLC Komersial - Kusuma, Enas Dhuhri; Nugroho, Nifwan Arbi; Suwastono, Addin; Sumaryono, Sujoko (Politeknik Negeri Batam, 2024)
Conventional PLCs are usually expensive and less flexible. PLC manufacturers generally design their PLCs that they can only be programmed by software they have distributed themselves. This makes it difficult for educational facilities such as universities to train PLC operators. One alternative way to train PLC operators is to use the OpenPLC device. OpenPLC is a relatively inexpensive open source PLC device that is designed to work like a conventional PLC in terms of both hardware and software. This paper will discuss the performance comparison between a conventional PLC and the OpenPLC system. Several points that will be described in this paper include memory size, scan time, and logic expressions. This paper will also discuss several features available in one of the PLC variants. At the end of the section, the advantages and disadvantages of PLC and OpenPLC will be discussed along with their utilizations.